Prevalence of food insecurity at household level and its associated factors in rural Puducherry: A cross-sectional study - Bharathnag Nagappa; Tanveer Rehman; Yamini Marimuthu; Shanthosh Priyan; Gokul Sarveswaran; S Ganesh Kumar (Indian Journal of Community Medicine, 2020)
Background: Malnutrition is a consequence of food insecurity. Food insecurity in India became a public health problem due to explosive population growth and widening gap between rich and poor. It also has a detrimental effect on factors related to health and social well-being of the family. Objectives: The study was conducted to determine the prevalence of food insecurity at household level in rural population and factors associated with it. Subjects and Methods: A community-based cross-sectional study was conducted among the households of rural Puducherry. The adult females in the households were interviewed with a pretested semi-structured questionnaire in which, along with sociodemographic factors, food insecurity was assessed using the Household Food Insecurity Access Scale. Univariate and multivariate logistic regression analysis was done to identify the factors associated with food insecurity. Results: Out of 299 households that were assessed for food insecurity, 31.7% (95% confidence interval [CI]: 26.6–37.4) had food insecurity. Out of 95 households with food insecurity, 51 (17%), 37 (13%), and 7 (2%) had severe, moderate, and mild food insecurity, respectively. In univariate analysis, the presence of children in the family, using below poverty line ration card, and socioeconomic status were significantly associated with food insecurity. In multivariate analysis, socioeconomic status was significantly associated with food insecurity (rate ratio: 3.59; P < 0.001 [95% CI: 1.68–7.67]). Conclusions: One in three families experienced the food insecurity, and it was more among households with children. It has to be addressed to prevent nutrition-related disorders in community, particularly in children.